2021
DOI: 10.1080/00958964.2021.1981207
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the desire of children to return to nature: Emotions in the face of environmental and intergenerational injustices

Abstract: the global cOViD-19 public health crisis has driven policies of lockdowns and social distancing that have had negative social and economic impacts, worsening inequalities and social exclusions, and mixed environmental impacts. this study engaged children from schools with diverse environmental pedagogies in online focus groups about nature and their experiences with nature during the pandemic. Participants expressed fear of the unknown virus, sadness from isolation, longing for family and friends, and yearning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 35 publications
0
11
0
4
Order By: Relevance
“…Consequently, the data provided by this study are consistent with the hypothesis that the drawings in the sample reflect a learning loss due to the school closures following the outbreak of the COVID-19 pandemic. In this regard, it should be noted that, during the lockdowns, environmental and outdoor school activities were moved to the virtual world, and although online activities played a key role in maintaining access to school, the truth is that this situation implied a loss of sensory experiences and emotional connection with nature [ 28 ]. Thus, crucial areas of the comprehension of flora, such as the variety of plant specimens, the anatomical details of plants, and the ecological links between plants and animals, could have been affected by the lack of schooling in the 2019/20 academic year.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the data provided by this study are consistent with the hypothesis that the drawings in the sample reflect a learning loss due to the school closures following the outbreak of the COVID-19 pandemic. In this regard, it should be noted that, during the lockdowns, environmental and outdoor school activities were moved to the virtual world, and although online activities played a key role in maintaining access to school, the truth is that this situation implied a loss of sensory experiences and emotional connection with nature [ 28 ]. Thus, crucial areas of the comprehension of flora, such as the variety of plant specimens, the anatomical details of plants, and the ecological links between plants and animals, could have been affected by the lack of schooling in the 2019/20 academic year.…”
Section: Discussionmentioning
confidence: 99%
“…Also Lõhmus et al (2021) found that more greenery around the home is associated with fewer symptoms of depression and anxiety. In this context, however, Sharifi and Khavarian-Garmsir (2020) and Rios et al (2021) point to the "environmental injustice" resulting from the COV-ID-19 pandemic. Children from families with higher socio-economic status are more likely to have "holiday homes" in rural areas with large gardens.…”
Section: Discussionmentioning
confidence: 99%
“…In research from England, 75.7% of urban parents said the lockdowns had caused them to change their attitudes to the importance of access to green space for their children (Howlett and Turner 2022 ). Research also shows that the lockdowns accentuated a desire to connect to the natural world for children’s improved wellbeing and to improve their relationship with nature (Quay et al 2020 ; Pouso et al 2021 ; Rios et al 2021 ). This has potential significance in relation to the commitment to the United Nations commitment to human and planetary wellbeing (United Nations 2021 ).…”
Section: Introductionmentioning
confidence: 99%